The association between hypertension self-management and stroke event in male patients at the Badung District Hospital, Bali - Ni Kadek Sutini; Ni Wayan Septarini; I Made Ady Wirawan; Anak Agung Sagung Sawitri (Universitas Udayana, 2018)
Background and purpose: Hypertension is a major risk factor for stroke. Despite efforts to control hypertension with pharmacological and non-pharmacological therapies, the prevalence of and death from stroke is reported to be increasing. This study aims to determine the association of hypertension self-management with the incidence of stroke in patients with hypertension. Methods: A case-control study was conducted involving 44 patients suffering from hypertension and who had suffered a stroke as cases, as well as 44 patients with hypertension and without stroke as controls. Cases and controls were conveniently selected at the outpatient clinic of Badung District Hospital. Data on self-management of diet, physical activity, stress mitigation efforts, alcohol consumption, and medication adherence were collected using self administered questionnaire. Data on the diagnosis of hypertension, stroke and history of comorbidities were obtained from the patient’s medical records. Multivariate analysis using logistic regression was employed to assess the association between hypertension self-management with the incidence of stroke in patients with hypertension. Results: Characteristics of cases and controls did not differ in education, marital and socioeconomic status, but differed in age and employment. Multivariate analysis showed that there were three components of hypertension self-management associated with the incidence of stroke, namely poor adherence to medication (AOR=7.28; 95%CI: 2.19-24.17), poor self-management of stress (AOR=5.45; 95%CI: 1.56-18.99), and poor management of self-regulated diet (AOR=5.28; 95%CI: 1.31-21.32). Conclusion: Medication adherence, diet and stress management are the three main components of self-management that are associated with stroke events among hypertension patients. Efforts to increase medication adherence, diet and stress management should be enhanced.